Penerapan Pendekatan Tutorial pada Pembelajaran Servis Atas Bola Voli di Smp Negeri 13 Lubuklinggau - Muhammad Suhdy; Muhammad Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The tutorial approach is basically the same as the guidance approach, which aims to provide assistance to students or students in order to achieve optimal learning outcomes. The purpose of this study was to determine the improvement of the top service techniques in volleyball games by using a tutorial approach at SMP Negeri 13 Lubuklinggau.The method used in this study was Classroom Action Research (CAR) with the subject of this research being conducted at Grade VIII students of SMP Negeri 13 Lubuklinggau in the 2018/2019 academic year, totaling 36 students consisting of 18 male students and 18 female students of class V totaling 32 students. Data collection techniques using II (two) cycles. After the data is obtained, the data is processed using strugess rules.Based on the results of calculations and analysis of the data that has been described, it can be stated that the mastery of basic technical services for volleyball before and after the implementation of the first cycle has increased significantly, this can be seen from the average percentage of indicator I (throw up) before the implementation of the first cycle of 59.82% was classified as sufficient, in the first cycle of 75.56% was classified as good and in the second cycle of 86.48% was classified as very good; indicator II (hitting the ball) before the implementation of the first cycle of 60.22% was classified as sufficient, in the first cycle of 73.33% was classified as sufficient and in the second cycle of 85.58% was classified as very good; and indicator III (follow through) before the implementation of the first cycle of 60.28% is quite sufficient, in the first cycle of 73.33% is sufficient and in the second cycle of 85% is quite good. Keywords: top service, Tutorial Approach